Deciphering the anti-filarial potential of bioactive compounds from Ocimum sanctum: a combined experimental and computational study - Ayushi Mishra; Vipin Kumar; Anchal Singh (Taylor & Francis Group, 2022)
Context The anthelminthic effect of Ocimum species (Lamiaceae) has been reported, however, its anti-filarial effect has not been explored to date.Objective This study evaluates the effect of Ocimum sanctum L. (OS) against lymphatic filarial parasites.Material and methods The ethanol extract of OS (EOS) leaves was tested for anti-filarial activity against Setaria cervi. Equal size and number (n = 10) of adult female S. cervi worms were incubated in 125, 250 or 375 μg/mL EOS extract for 6 h at 37 °C. The OS bioactive components were identified by UPLC-ESI-MS/MS and subjected to docking and molecular dynamics (MD) simulation against filarial antioxidant proteins.Results The EOS significantly inhibited the motility of adult female S. cervi after 6 h of incubation. The motility was found to be reduced by 53.7% in 375 µg/mL and 43.8% in 250 µg/mL EOS after 6 h of treatment. The UPLC-ESI-MS/MS analysis of ethanol extract of O. sanctum revealed the presence of 13 bioactive compounds. The docking analysis showed eight OS bioactive compounds to have high binding affinity (> 4.8 kcal/mol) towards antioxidant proteins of filarial parasites. Additionally, MD simulation studies showed significant impact of (RMSD ≤ 10 Å) chlorogenic acid, luteolin and ursolic acid on filarial antioxidant enzymes/proteins. To our knowledge, this is the first report of the anti-filarial activity of Ocimum sanctum.Discussion and conclusions The effect of EOS and OS bioactive components on human filarial parasites can be further evaluated for the development of new anti-filarial formulations.